PEMANFAATAN LIMBAH CANGKANG BIJI KARET DENGAN ADITIF TEMPURUNG KELAPA SEBAGAI BAHAN BAKAR ALTERNATIF MELALUI TEKNOLOGI PEMBRIKETAN - Randi Nasarudin; Abdul Ghofur (JTAM ROTARY, 2019)
The development of alternative energy sources that can replace fuel oil is very important to utilize natural resources optimally and environmentally. The shell produced from rubber plants is the main ingredient in this study, while the coconut shell is an additional material used to increase the calorific value of alternative fuels which is often referred to as Briquette. The purpose of this study is to determine the effect of variations in raw material composition and variations in pressure on the quality of rubber shells and coconut shell waste briquettes according to SNI standards. The raw material for rubber shell and coconut shell is processed into charcoal using carbonization method with a variation of a mixture of 85%: 15%, 90%: 10% and 95%: 5% with 5% adhesive. Then mix the printed material with a pressure of 300 kg/cm2 and 100kg/cm2. The quality parameters of briquettes are based on SNI 01-6235-2000 standards with moisture content, ash content, volatille matter content, and lacquer value. The results of the study showed that the sample b1 with 85% injection: 15% print pressure 300kg/cm2. The briquette with the sample code b1 has a water content value of 5,10432%, ash content of 14,8604%, volatile matter content of 12,8002%, carbon value of 66,8225% and heating value of 6576.592501 cal/gr. But overall the briquettes have not met the standards of SNI 01-6235-2000 concerning the quality of wood charcoal briquettes. Because the ash content of the briquette exceeds the maximum limit that has been determined, namely a maximum of 8%.  Keywords: Alternative Energy, Rubber Seed Shell, Coconut Shell, Pressure